Practical application to a network operation center - Laura Lebrato Álvaro; Alberto Román Perela (Centro de Estudios Financieros, 2015)
This project involves the management of a network operations center using a web application that simulates the operations of these centers. We analyze the operation and management of the spanish electricity system, what its functions and objectives are highlighting the similarities between the application and the real system. Considering the importance of the power matrix in the electricity system, we explain the power plants available in the application, the types and operation of each production technology is exposed giving special importance the maintenance which directly affects the cost and electricity production. One of the most interesting installations of the application is the high voltage direct current transformer since electricity transport traditionally has been performed in alternating current. Following the study, an increase is seen in the use of renewable sources for generating electricity in recent years. Its participation in the spanish power matrix is almost equal to that of conventional energy sources, although, because many renewable sources depend on weather conditions, they cannot completely replace conventional sources with current technology.